Pengaruh Persepsi Kegunaan, Persepsi Kemudahan, Kepercayaan, Persepsi Kenyamanan, dan Persepsi Kecocokan Terhadap Sikap Pengguna Internet Banking - Santosa, Bobby Kurniawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The Effect of Function, Ease, Trustworthy, and Conformity Perception toward Client’s Behavior on Internet Banking System. The purpose of this research intend to examine the factors that affect the use behavior of the internet banking. The modified model of Technology Acceptance Model (TAM) which developed by Davis (1989) has literally performed to test various affected factors through the client’s behaviour of operating internet banking service. Apparently, the obtaining data was using survey method, which the study result showed the function, ease, trustworthy, and conformity perception have given an impact towardclient’s internet banking outlook. The implication of this study could be imposed on the relevancy of this study for bank’s management and internet banking analyst to imply an evaluation carefully to the function, ease, trustworthy, and conformity perception on developing the internet banking service.Keywords: Technology Acceptence Model (TAM), internet banking, functional perception, ease perception, trustworthy perception, and conformity perception, client’s behaviour.